بونیادی گێڕانەوەیی لە شیعری نوێی كوردیدا - ئەمین, محەمەد دلێر; محەمەد, بوشرا قادر كاكە (Sulaimani Journal for Humanities, 2022)
Titled “Narrative Structure in Modern Kurdish Poetry “, this paper is a brief and truncate study from a PhD thesis that goes under the name of “Narrative Aesthetics in Modern Kurdish Poetry”. ‏Emphasizing and highlighting modern Kurdish poetry is the main idea of this work, which in turn has numerous dimensions, we picked one type among them and that being “Narrative Poetry”. What is meant by narration is ,it shows series of events in a precise and artistic type of way so that the reader can visualize and grasp meaning of things he/she has yet to encounter, by another explanation, one has neither seen nor experienced. After all, this type of poetry mostly recognized by narrating a story or tale where poetic language and poetic form is predominant. In this style of poetry especially if the poem is in a long form, it is called “epic poetry, lyro-epic and open poetry “. However sometimes the poem is in a narrative form but because it is short or in a form of poster poetry or short poems, there is no specific address for it or the poet didn’t give it any specific names so we’ve included it in the narrative poetry category. We have shed light on two important points regarding narrative poetry in this study. The first one is how creatively along with the use of poetic language and rhetoric, the poet expressed his/her sense of aestheticism, and this way of expression is distinguishing traits of a poem. We also talked about the importance of poetic imagery and the structural parts of poetic imagery for example” metaphor, allegory, and metonymy” which are the building blocks of aestheticism of a poem. Secondly, we talked about the structures of a story and those apparent elements that shapes a particular story and without them, the narration would be incomplete, like “description, character, time, place, and event”. ‏ At the end of each statement, with samples of modern Kurdish poetry we showed the intersection of these two substantial essence of art and literature, which together they formed a new kind of poetry that have structural and constructive traits of both a poem and a story.
Keywords: narration; lyroepic; modern Kurdish poetry; structure of a story; aestheticism